Sulfonate Thiacalixarene-Modified Polydiacetylene Vesicles as Colorimetric Sensors for Lead Ion Detection - Angelina A. Fedoseeva; Indira Yespanova; Elza D. Sultanova; Bulat Kh. Gafiatullin; Regina R. Ibragimova; Klara Kh. Darmagambet; Marina A. Il’ina; Egor O. Chibirev; Vladimir G. Evtugyn; Nurbol O. Appazov; Vladimir A. Burilov; Svetlana E. Solovieva; et al. (Colloids and Interfaces)
We report the first synthesis of zwitterionic thiacalixarenes featuring imidazolium and sulfonate groups on the upper rim and alkyl (butyl or octyl) fragments on the lower rim of the platform. Despite their amphiphilic structure, these macrocycles exhibit limited water solubility. However, dynamic light scattering detected the formation of associates for derivatives with octyl moieties at a concentration of 0.1 mM. To develop stable materials for aqueous environments and to investigate the functionality of zwitterionic sulfonate-imidazolium groups along with the thiacalixarene platform, mixed organo-organic systems based on polydiacetylene polymer were created. Characterization of the modified polydiacetylene systems through various analytical methods revealed a significant colorimetric response to lead ions in aqueous media, surpassing that of the unmodified polydiacetylene polymer. Additionally, the modified polymers demonstrated efficacy in purifying aqueous media from lead ions, as evidenced by anodic stripping voltammetry (ASV) and microwave plasma atomic emission spectroscopy (MP AES).